2013
DOI: 10.2134/agronj2012.0071
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Forage Sorghum to Polymer under Water Deficit Conditions

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is among the most important warm-season forages that is grown in mainly arid and semiarid regions of southeastern Iran. Irrigation water is an energy-intensive input and it is also becoming scarce and costly in this country. Soil application of polymeric materials such as Superab A200 (SAP) can increase soil water storage capacity and increase water use effi ciency (WUE). Th e objective of this study was to investigate the eff ect of diff erent rates of SAP and irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…During harvesting, grain yield was calculated. For measuring the relative water content, the highest young leaf was selected, and it's wet, saturated and dry weights were determined, and RWC was calculated by using the following formula (Fazeli-Rostampour et al,2013):…”
Section: Methodsmentioning
confidence: 99%
“…During harvesting, grain yield was calculated. For measuring the relative water content, the highest young leaf was selected, and it's wet, saturated and dry weights were determined, and RWC was calculated by using the following formula (Fazeli-Rostampour et al,2013):…”
Section: Methodsmentioning
confidence: 99%
“…The amount of irrigated water was calculated for each treatment based on the total water requirement, and by random sampling from three different parts of each plot and determining the percentage of soil water content; the amount was calculated at about Rafat where, ETC and ETO are the plant and reference evapotranspirations, Kpan and Ep are the pan coefficient, respectively (Allen et al, 1998;Fazeli Rostampour et al, 2013). Total volumes of irrigation water applied in the control treatment (Irrigation after 70 mm of evaporation) were 4885.7 and 5026.4 m 3 in 2015 and 2016, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Dry application rates ranged from 75 (0.003% BM) to 225 kg ha −1 (0.015% BM) and wet application rate was 18 g m −3 . The greatest application rate used in the Fazeli Rostampour, Yarnia, Rahimzadeh Khoee, Seghatoleslami, and Moosavi (2013) sandy loam soil study, 225 kg ha −1 (0.015% BM), increased relative water content (WC related to WC at full turgor) from 66 to 76% while the lowest application of SAP, 75 kg ha −1 (0.003% BM), only increased to 70%. The same authors found a significant increase in WUE from 2.1 to 2.6−2.9 kg dry mass produced per m 3 of water for 75, 150, and 225 kg ha −1 (0.003, 0.007, and 0.015% BM) of SAP application (Fazeli Rostampour et al., 2013).…”
Section: Superabsorbent Polymer Effects On Soil Propertiesmentioning
confidence: 97%
“…Under water stress conditions SAPs have a greater influence on plant productivity (Fazeli Rostampour et al., 2013; Egrinya Eneji et al., 2013) compared with nonstressed conditions. Sorghum [ Sorghum bicolor (L.) Moench] dry matter only increased when there was a water deficit in sandy loam soil with SAP application rate of 75, 150 or 225 kg ha −1 (0.003, 0.007, 0.015% BM) (Fazeli Rostampour et al., 2013). At the application rate of 30 kg ha −1 (0.001% BM) to a sandy loam soil, corn biomass increased 99% under deficit irrigation and 39% under moderate irrigation, and only 11% under full irrigation; overall, plants under water deficit showed reduced stress signals with SAP application compared with no SAP (Eneji et al., 2018).…”
Section: Superabsorbent Polymer Effects On Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation